Addition of glycosylation to influenza A virus hemagglutinin modulates antibody-mediated recognition of H1N1 2009 pandemic viruses - Job, Emma R. (2013)
Seasonal influenza A viruses (IAV) originate from pandemic IAV and have undergone changes in antigenic structure, including addition of glycans to the viral hemagglutinin (HA). Glycans on the head of HA promote virus survival by shielding antigenic sites, but highly glycosylated seasonal IAV are inactivated by soluble lectins of the innate immune system. In 2009, human strains of pandemic H1N1 [A(H1N1)pdm] expressed a single glycosylation site (Asn104) on the head of HA. Since then, variants with additional glycosylation sites have been detected, and the location of these sites has been distinct to those of recent seasonal H1N1 strains. We have compared wild-type and reverse-engineered A(H1N1)pdm IAV with differing potential glycosylation sites on HA for sensitivity to collectins and to neutralizing Abs. Addition of a glycan (Asn136) to A(H1N1)pdm HA was associated with resistance to neutralizing Abs but did not increase sensitivity to collectins. Moreover, variants expressing Asn136 showed enhanced growth in A(H1N1)pdm-vaccinated mice, consistent with evasion of Ab-mediated immunity in vivo. Thus, a fine balance exists regarding the optimal pattern of HA glycosylation to facilitate evasion of Ab-mediated immunity while maintaining resistance to lectin-mediated defenses of the innate immune system.